2024
DOI: 10.3390/biom14010104
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Metalloproteomics

James P. C. Coverdale,
Sirilata Polepalli,
Marco A. Z. Arruda
et al.

Abstract: Interactions between proteins and metal ions and their complexes are important in many areas of the life sciences, including physiology, medicine, and toxicology. Despite the involvement of essential elements in all major processes necessary for sustaining life, metalloproteomes remain ill-defined. This is not only owing to the complexity of metalloproteomes, but also to the non-covalent character of the complexes that most essential metals form, which complicates analysis. Similar issues may also be encounter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 189 publications
1
0
0
Order By: Relevance
“…Taken together, these results demonstrate that in vitro studies can provide useful insight into dynamic aspects of the toxicological chemistry of individual metal(loid) species in blood plasma and that ternary interactions between a toxic metal(loid) species, a plasma protein and a SMW metabolite (e.g., Cys, hCys and/or others) that unfold in the presence of 100 mM Cl − play an important role in the selective delivery of their 'cargo' to toxicological target organs. These findings are reminiscent of previously observed interactions between Cu 2+ , HSA and L-histidine [95], the kinetic aspects of which are still not completely understood [96], and conceptually related studies which have demonstrated that the binding of Zn 2+ to HSA is modified by the fatty acid myristate, with health-relevant ramifications in the organs downstream [97]. While it cannot be entirely excluded that Hg 2+ -induced conformational changes of HSA [98] play an important role in its translocation to target organs, the obtained results suggest that probing ternary interactions between other neurotoxic metal(loid) species, such as Mn 2+ , As III and Pb 2+ with their known plasma proteins and distinct SMW metabolites in the presence of 100 mM NaCl may be a fruitful strategy to uncover the biomolecular mechanisms that deliver their cargo to uptake mechanisms at the blood-brain-barrier (BBB), which is a prerequisite for their subsequent uptake into the brain to cause neurotoxicity.…”
Section: Advances In the Toxicological Chemistry Of Metal(loid)s In B...supporting
confidence: 74%
“…Taken together, these results demonstrate that in vitro studies can provide useful insight into dynamic aspects of the toxicological chemistry of individual metal(loid) species in blood plasma and that ternary interactions between a toxic metal(loid) species, a plasma protein and a SMW metabolite (e.g., Cys, hCys and/or others) that unfold in the presence of 100 mM Cl − play an important role in the selective delivery of their 'cargo' to toxicological target organs. These findings are reminiscent of previously observed interactions between Cu 2+ , HSA and L-histidine [95], the kinetic aspects of which are still not completely understood [96], and conceptually related studies which have demonstrated that the binding of Zn 2+ to HSA is modified by the fatty acid myristate, with health-relevant ramifications in the organs downstream [97]. While it cannot be entirely excluded that Hg 2+ -induced conformational changes of HSA [98] play an important role in its translocation to target organs, the obtained results suggest that probing ternary interactions between other neurotoxic metal(loid) species, such as Mn 2+ , As III and Pb 2+ with their known plasma proteins and distinct SMW metabolites in the presence of 100 mM NaCl may be a fruitful strategy to uncover the biomolecular mechanisms that deliver their cargo to uptake mechanisms at the blood-brain-barrier (BBB), which is a prerequisite for their subsequent uptake into the brain to cause neurotoxicity.…”
Section: Advances In the Toxicological Chemistry Of Metal(loid)s In B...supporting
confidence: 74%